Synthesis and Anticancer Activity of 9-O-Pyrazole Alkyl Substituted Berberine Derivatives - Xiao, Daipeng; He, Fen; Peng, Dongming; Zou, Min; Peng, Junying; Liu, Pan; Liu, Yanfei; Liu, Zhenbao (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: Berberine (BBR), an isoquinoline plant alkaloid isolated from plants such as Coptis chinensis and Hydrastis canadensis, own multiple pharmacological activities. Objective: In this study, seven BBR derivatives were synthesized and their anticancer activity against HeLa cervical and A549 human lung cancer cell lines were evaluated in vitro. Methods: The anti-cancer activity was measured by MTT assay, and apoptosis was demonstrated by the annexin V-FITC/PI staining assay. The intracellular oxidative stress was investigated through DCFH-DA assay. The molecular docking study was carried out in molecular operating environment (MOE). Results: Compound B3 and B5 showed enhanced anti-cancer activity compared with BBR, the IC50 for compound B3 and B5 were significantly lower than BBR, and compound B3 at the concentration of 64 or 128 μM induced apoptosis in HeLa and A549 cell lines. The reactive oxygen species (ROS) was generated in both cell lines when treated with 100 μM of all the compounds, and compound B3 and B5 induced higher activity in the generation of ROS, while compound B3 exhibited the highest activity, these results are in accordance with the cytotoxicity results, indicating the cytotoxicity were mostly generated from the oxidative stress. In addition, molecular docking analysis showed that compound B3 had the greatest affinity with Hsp90. Upon binding, the protective function of Hsp90 was lost, which might explain its higher cytotoxicity from molecular interaction aspect. Conclusion: All the results demonstrated that compound B3 and B5 showed significantly higher anti-cancer ability than BBR, and compound B3 is a promising anticancer drug candidate.
Keywords: anti-cancer